Aerobic training increases the expression of adiponectin receptor genes in the peripheral blood mononuclear cells of young men - SH Lee; HR Hong; TK Han; HS Kang (Termedia Publishing House, 2015)
Little is known about the effect of exercise training on the expression of adiponectin receptor genes in peripheral blood mononuclear cells (PBMCs). In this study, we investigated the effects of aerobic training on the expression of AdipoR1 and AidpoR2 mRNAs in PBMCs, whole body insulin sensitivity, and circulating adiponectins in men. Thirty young men were randomly assigned to either a control (n=15) or an exercise (n=15) group. Subjects assigned to the exercise group underwent a 12-week jogging and/or running programme on a motor-driven treadmill at an intensity of 60%-75% of the age-based maximum heart rate with duration of 40 minutes per session and a frequency of 5 days per week. Two-way mixed ANOVA with repeated measures was used to test any significant time-by-group interaction effects for the measured variables at p=0.05. We found significant time-by-group interaction effects for waist circumference (p=0.001), VO2 max (p<0.001), fasting insulin (p=0.016), homeostasis model assessment for insulin resistance (HOMA-IR) (p=0.010), area under the curve (AUC) for insulin response during the 75-g oral glucose tolerance test (p=0.002), high-molecular weight (HMW) adiponectin (p=0.016), and the PBMC mRNA levels of AdipoR1 (p<0.001) and AdipoR2 (p=0.001). The exercise group had significantly increased mRNA levels of AdipoR1 and AdipoR2 in PBMCs, along with increased whole body insulin sensitivity and HMW adiponectin, decreased waist circumference, and increased VO2 max compared with the control group. In summary, the current findings suggest that exercise training modulates the expression of AdipoR1 and AdipoR2 mRNAs in PBMCs, implying that manipulation of the expression of these genes could be a potential surrogate for lifestyle intervention-mediated improvements of whole body insulin sensitivity and glucose homeostasis.